SEJARAH PEMEKARAN KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR - Yulia Gustina; Ridwan Melay; Tugiman Tugiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Koto Kampar Hulu was a new expanded Sub-district at 11 June 2010 based on the rgulation of Kampar district number 2 year 2010, regarding to the change of the regulations at Kampar district number 22 year 2003, rgarding to the forming of the Bangkinang Seberang, Salo, Kampar Utara. Rumbio Jaya, Kampar Timur, Kampar Kiri Tengah, Gunung Sahilan, Perhentian Raja and Koto Kampar Hulu district. Koto Kampar Hulu has thousand villages. 5 local villages and an Ex-Transmigration vilage (transfer from XIII Koto kampar) with the names of villages as follows : Tanjung village, Tabing vlllage, Pongkai village (ex-transmigration), Gunun Malelo village, Sibiruang village, Bandur Picak village. The purposes of this study are 1) to find out the histoy of the expansion of Koto Kampar Hulu sub-disrict. 2) to finid out the fulfillment regional expansion requirements. 3) to find out the supporting and inhibiting factors in development of Koto Kampar Hulu sub-district expansion. 4) to find out the effects of expansion in Koto Kampar Hulu sub-disrict at education field. This research use qualitative method wih desciptive presentation. The result of this research show that Koto Kampar Hulu sub-district was a combination villages from XIII Koto Kampar sub-district which want their area to be devided with the aim of facilitating public to connect with the sub-district and to close the distance to the previous sub-district.Key Words: Sub-district expansionJOM